Public Discourses of Climate Change in Hong Kong. Issue 1 (1st January 2016) - Lo, Alex Y.
Abstract: The changing political environment in Hong Kong is likely to accelerate the transition in environmental policy discourse. Opportunities for critical public involvement are increasing and new environmental discourses are emerging. Yet, previous social surveys did not explore the range of these discourses and few focused on climate change. The paper outlines the public discourses of climate change in Hong Kong. Using Q-methodology, four distinctive discourses were identified, namely Pure Environmentalism, Political Pragmatism, Popular Optimism, and Fair Rationalism. While the first one is climate-centric, the other three are political or social in nature and do not indicate a clear or coherent climate orientation. This suggests that the climate change concern of the Hong Kong public is not tightly embedded into a coherent narrative of social and institutional transformation. Effective climate change governance and policies require strengthening the link between such concern and the public desires for social and institutional transformation. Bringing together the ongoing social movements and environmental campaigns will be instrumental to nurture an active climate citizenry.